Bonding material and method for manufacturing bonded body
By using adhesive materials with roughly spherical metal particles and performing pressure sintering under low pressure conditions, the problems of semiconductor chip rupture and substrate deformation caused by high-voltage melting in the prior art are solved, and the density and thermal conductivity of the adhesive layer with a larger thickness are improved.
Patent Information
- Application Number
- JP2024546260
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-04-25
- Filing Date
- 2024-04-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-04-19
AI Technical Summary
In the prior art, when silver or copper particles are used as bonding materials, high-pressure melting may lead to cracking of semiconductor chips and deformation of substrates, while the bonding layer with increased thickness is prone to cracks during drying.
Adhesive materials containing substantially spherical metal particles (D50 0.3-0.5 μm, Dmin > 0.08 μm) were used and pressure sintered after drying at low pressure (approximately 20 MPa or less) to form a compact adhesive layer with fewer holes.
The cracks of the adhesive material after drying are effectively suppressed, and an adhesive layer with fewer hollows is formed under low pressure conditions, which improves the density and thermal conductivity of the adhesive layer.
Smart Images

Figure 0007648014000003 
Figure 0007648014000004 
Figure 0007648014000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a bonding material and a method for manufacturing a bonded body. This application claims priority based on Japanese Patent Application No. 2023-071339, filed on April 25, 2023, the contents of which are incorporated herein by reference. [Background technology]
[0002] Silver and copper are considered promising as raw materials for bonding materials to replace solder when bonding conductive parts together, because of their high thermal conductivity and high melting point. In particular, silver and copper are highly anticipated as packaging materials for power semiconductors, which have high heat density. However, when using a bonding material containing silver particles or copper particles, the bonding material is usually sintered at a temperature condition below the melting point of these metals to bond conductive parts together (in other words, sintered diffusion bonding). Therefore, the bond formed by sintering becomes a porous body containing many voids inside. However, when the operating temperature of the semiconductor fluctuates greatly, thermal stress is generated in the bond, and these voids become a concentration source, causing damage to the bond. Furthermore, the thermal conductivity of the bond where voids exist is reduced. Therefore, it is preferable that the number of voids generated inside the bond is small.
[0003] On the other hand, in order to form a dense sintered film with few voids, a method is usually adopted in which the bonding material is heated and at the same time, the laminate of the conductive parts and the bonding material is pressed in the lamination direction. As a method for forming such a sintered film, for example, a method is disclosed in which a bonding material containing silver nanoparticles (particle diameter 20 nm) is used to heat a laminate of the conductive parts and the bonding material at 300°C while pressing at a pressure of 60 MPa to form a sintered film with a porosity of about 2.5%. It is also disclosed that a sintered film with a porosity of about 8% was formed using a bonding material containing silver nanoparticles (particle diameter 18 nm), silver submicron particles (particle diameter 150 nm), and silver micron particles (particle diameter 5063 nm) (see Non-Patent Document 1). In this way, a bonded body obtained by bonding conductive parts together using a bonding material containing silver nanoparticles has the advantage of being highly resistant to thermal shock tests and highly reliable. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Degradation Mechanism of Pressure-Assisted Sintered Silver by Thermal Shock Test,Energies 2021,14, 5532 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the method described in Non-Patent Document 1, applying a high pressure of 60 MPa poses the risk of cracking the semiconductor chip and deforming the substrate, and furthermore, the press machine used during application of pressure requires frequent maintenance. In order to avoid these problems, it is necessary to keep the pressure during application at 20 MPa or less, but Non-Patent Document 1 does not disclose such a means. Furthermore, in the method described in Non-Patent Document 1, when the thickness of the joint (sintered film) is increased, particularly when the thickness is made 100 μm or more, cracks may easily occur due to shrinkage of the dried material when the joining material is dried in the process of forming the joint.
[0006] The present invention has an object to provide a bonding material for forming a joint that joins conductive parts together, which can suppress cracking when forming a joint from the bonding material even if the dried bonding material is thick, and can form a joint with few voids even when the dried bonding material is fired while being pressurized at a low pressure of about 20 MPa or less. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention employs the following configuration. [1] A bonding material for bonding conductive parts together, comprising metal particles including substantially spherical metal particles (A) and a solvent for dispersing the metal particles, wherein a particle diameter D50 of the metal particles (A) at 50% cumulative volume, as measured by a laser diffraction / scattering particle size distribution measurement, is 0.3 to 0.5 μm, and a minimum particle diameter Dmin of the metal particles (A) is greater than 0.08 μm. [2] The bonding material according to [1], wherein the metal particles include metal particles (B) different from the metal particles (A), and a minimum particle size Dmin of the metal particles (B) measured by a laser diffraction / scattering particle size distribution measurement is greater than 0.08 μm. [3] The bonding material according to [1] or [2], further comprising a resin component in the solvent, the resin component being a curable resin, a non-curable resin, or a thermoplastic resin, and the ratio of the content of the resin component to the content of the metal particles in the bonding material is less than 0.01 mass%. [4] The bonding material according to [1] or [2], wherein the solvent does not contain a resin component which is a curable resin, a non-curable resin, or a thermoplastic resin. [5] The bonding material according to any one of [1] to [4], wherein the metal particles (A) have a volume-based 90% cumulative particle diameter D90 of less than 0.8 μm as measured by a laser diffraction / scattering particle size distribution measurement. [6] The bonding material according to any one of [1] to [5], wherein the metal particles (A) and the metal particles (B) are both silver particles. [7] The specific surface area of the metal particles (A) is 0.95 to 1.5 m 2 The bonding material according to any one of [1] to [6], wherein the bonding strength is in the range of / g.
[0008] [8] A method for manufacturing a bonded body in which a first conductive part and a second conductive part are bonded via a conductive bonding part, the method comprising the steps of: attaching a bonding material described in any one of [1] to [7] to a first surface of the first part or a second surface of the second part; drying the attached bonding material to form a dried bonding material; stacking the first part and the second part with the dried bonding material interposed therebetween to produce a laminate; and forming the bonded part from the dried bonding material by firing the dried bonding material in the laminate at a temperature higher than the temperature at which the bonding material was dried. [9] The method for producing a bonded body according to [8], wherein the thickness of the bonded portion is 100 μm or more. Effect of the Invention
[0009] According to the present invention, there is provided a bonding material for forming a joint that joins conductive parts together, which can suppress cracking when forming a joint from the bonding material even if the dried bonding material is thick, and can form a joint with few voids even when the dried bonding material is fired while being pressurized at a low pressure of about 20 MPa or less. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view showing a schematic example of a bonded body to which a manufacturing method according to an embodiment of the present invention is applied; [Figure 2A] FIG. 2 is a cross-sectional view for illustrating a typical example of a method for producing a bonded body according to an embodiment of the present invention, and is a view for illustrating a bonding step. [Figure 2B] FIG. 2B is a diagram for explaining a drying step following the step in FIG. 2A. [Figure 2C] FIG. 2C is a diagram for explaining a lamination step following the step in FIG. 2B. [Figure 2D] FIG. 2D is a diagram for explaining a firing step following the step in FIG. 2C. [Figure 2E] FIG. 2F is a view for explaining a bonded body after the step of FIG. 2E. [Figure 3A] FIG. 11 is a cross-sectional view for illustrating a schematic example of a method for producing a bonded body according to an embodiment of the present invention, and is a view for illustrating a bonding step. [Figure 3B] FIG. 3B is a diagram for explaining a drying step following the step in FIG. 3A. [Figure 3C] FIG. 3C is a diagram for explaining a lamination step following the step in FIG. 3B. [Figure 3D] FIG. 3D is a diagram for explaining a firing step following the step of FIG. 3C. [Figure 3E] FIG. 3F is a view for explaining a bonded body after the step of FIG. 3E. [Figure 4] 1 shows imaging data of metal particles (A)-1 used in Example 1, obtained by SEM. [Diagram 5] 1 shows imaging data of metal particles (A)-1 used in Example 2, obtained by SEM. [Figure 6] 1 shows imaging data of metal particles (B)-1 used in Comparative Example 1, obtained by SEM. [Figure 7] 1 shows imaging data of metal particles (B)-2 used in Comparative Example 2, obtained by SEM. [Figure 8] 1 shows imaging data of metal particles (B)-3 used in Comparative Example 3, obtained by SEM. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] ◇Joining material A bonding material according to one embodiment of the present invention comprises metal particles including substantially spherical metal particles (A) and a solvent for dispersing the metal particles, and the metal particles (A) have a particle diameter D50 of 0.3 to 0.5 μm at 50% cumulative volume, as measured by a laser diffraction / scattering particle size distribution measurement, and the metal particles (A) have a minimum particle diameter Dmin of greater than 0.08 μm. With this configuration, when forming a joint from the joint material, cracking of the dried joint material can be suppressed even if the dried joint material is thick. Also, in a laminate obtained by stacking conductive parts with the dried joint material, even if the dried joint material is fired while being pressurized at a low pressure of about 20 MPa or less, a joint with few voids can be formed.
[0012] The bonding material in this embodiment will be described below. In the bonding material, the total content of one or more components (described below) in the bonding material does not exceed 100 mass % with respect to the total mass of the bonding material.
[0013] <<Metal particles>> In the present embodiment, the metal particles contained in the bonding material include at least metal particles (A). The metal particles may further include metal particles (B), which will be described in detail later. The metal particles (A) are approximately spherical in shape. In this specification, the term "approximately spherical" refers to a shape that is spherical or can be considered as spherical, not limited to the case of metal particles (A), and more specifically refers to a particle shape in which the aspect ratio calculated by [long axis of particle] / [short axis of particle] is 2 or less. The aspect ratio is preferably 1.6 or less, more preferably 1.3 or less. The surface of the approximately spherical particle may be composed of only curved surfaces, or may be composed of flat surfaces, or may be composed of corners formed by connecting two flat surfaces at a predetermined angle to each other. The surface of the approximately spherical particle may be smooth or may have uneven parts. As the metal particles (A), any commercially available spherical or nearly spherical particles can be used as long as they satisfy the above particle size conditions.
[0014] The metal species of the metal particles (A) is preferably one having high thermal conductivity and a high melting point. For example, the thermal conductivity (e.g., thermal conductivity in bulk) of the metal species of the metal particles (A) is preferably 350 W / mK or more, and may be 350 to 450 W / mK, which allows heat to be quickly released even when the heat generated by a semiconductor or the like in contact with the bonding material reaches a high temperature (e.g., 150°C or more). For example, the melting point of the metal species of the metal particles (A) is preferably 900°C or higher, and may be 900 to 1100°C.
[0015] The metal species of the metal particles (A) contained in the bonding material may be only one type, or may be two or more types. When there are two or more types, the combination and ratio thereof can be selected arbitrarily.
[0016] Among them, the metal species of the metal particles (A) is preferably silver or copper, and more preferably silver. That is, the metal particles (A) are preferably silver particles or copper particles, and more preferably silver particles. The metal species of the metal particles (A) is not limited to pure silver or pure copper, and may be a silver alloy or a copper alloy.
[0017] Among the metal particles (A), examples of the silver particles include silver particles obtained by a reduction method and silver particles obtained by an atomization method. The silver particles may be surface-treated, the surface of which has been chemically treated (treated with a chemical substance), or may be surface-untreated, the surface of which has not been chemically treated. Usually, silver particles obtained by the reduction method are surface-treated, whereas silver particles obtained by the atomization method are surface-untreated.
[0018] <Metal particle size distribution> In this embodiment, the particle size distribution of the metal particles was measured by laser diffraction / scattering particle size distribution measurement. Hereinafter, the minimum particle diameter of metal particles measured by laser diffraction / scattering particle size distribution measurement will be referred to as "Dmin," the particle diameter at 10% cumulative volume of metal particles will be referred to as "D10," the particle diameter at 50% cumulative volume of metal particles will be referred to as "D50," the particle diameter at 90% cumulative volume of metal particles will be referred to as "D90," and the maximum particle diameter of metal particles will be referred to as "Dmax."
[0019] The D50 of the metal particles (A) is 0.3 to 0.5 μm, and may be, for example, any one of 0.3 to 0.4 μm, 0.45 to 0.5 μm, and 0.35 to 0.45 μm. When the D50 is equal to or greater than the lower limit, the effect of suppressing cracking of the dried bonding material is enhanced even if the dried bonding material is thick. When the D50 is equal to or less than the upper limit, the effect of forming a bonding part with fewer voids is enhanced even if the dried bonding material is fired while being pressurized at a low pressure.
[0020] The Dmin of the metal particles (A) is greater than 0.08 μm, and the bonding material does not need to contain metal particles (A) whose particle diameter is 0.08 μm or less. In other words, when the particle diameter of the metal particles (A) is measured on a volume basis by, for example, a laser diffraction / scattering type particle size distribution measurement, no particles having a particle diameter of 0.08 μm or less are observed. By using such metal particles (A), cracking of the dried bonding material can be suppressed even if the dried bonding material is thick.
[0021] The Dmin of the metal particles (A) is preferably greater than 0.08 μm and greater than 0.09 μm, and may be, for example, greater than 0.12 μm or greater than 0.15 μm. When the Dmin is in such a range, the effect of suppressing cracks in the dried bonding material is enhanced even if the dried bonding material is thick. On the other hand, Dmin is preferably 0.21 μm or less. Such metal particles (A) are easier to prepare and are more readily available. For example, particles having a D50 in the range of 0.3 to 0.5 μm and a Dmin greater than 0.21 μm (i.e., particles with a narrow particle size distribution) may be difficult to produce. In one embodiment, Dmin may be, for example, any one of greater than 0.08 μm and equal to or less than 0.21 μm, 0.09 to 0.21 μm, 0.12 to 0.21 μm, and 0.15 to 0.21 μm, although these are merely examples of Dmin.
[0022] The D90 of the metal particles (A) is not particularly limited, but is preferably less than 0.8 μm, more preferably 0.78 μm or less, and may be, for example, 0.72 μm or less, or 0.65 μm or less. When the D90 is in such a range, even if the dried bonding material is fired while being pressed at a low pressure, the effect of forming a bonding part with fewer voids is enhanced. On the other hand, D90 is preferably 0.45 μm or more. Such metal particles (A) are easier to prepare and are more readily available. For example, particles having D50 in the range of 0.3 to 0.5 μm and D90 smaller than 0.45 μm (i.e., particles with a narrow particle size distribution) may be difficult to produce. In one embodiment, D90 may be, for example, any one of 0.45 μm or more and less than 0.8 μm, 0.45 to 0.78 μm, 0.45 to 0.72 μm, and 0.45 to 0.65 μm or less, although these are merely examples of D90.
[0023] The D10 of the metal particles (A) is not particularly limited, but is preferably 0.18 μm or more, and may be, for example, 0.24 μm or more, or 0.3 μm or more. When the D10 is in such a range, even if the dried bonding material is thick, the effect of suppressing cracking of the dried bonding material is further increased. On the other hand, D10 is preferably 0.34 μm or less. Such metal particles (A) are easier to prepare and are more easily available. This is because, as described above, particles with a narrow particle size distribution may be difficult to manufacture. In one embodiment, D10 may be, for example, any one of 0.18 to 0.34 μm, 0.24 to 0.34 μm, and 0.3 to 0.34 μm, although these are merely examples of D10.
[0024] The Dmax of the metal particles (A) is preferably 2 μm or less. In other words, when the particle size of the metal particles (A) is measured on a volume basis by, for example, a laser diffraction / scattering particle size distribution measurement, it is preferable that no particles having a particle size larger than 2 μm are observed. Furthermore, Dmax may be, for example, 1.85 μm or less, or 1.7 μm or less. When Dmax is in such a range, the effect of forming a joint with fewer voids is further enhanced even when the dried joint material is fired while being pressurized at a low pressure. On the other hand, Dmax is preferably 1.5 μm or more. Such metal particles (A) are easier to prepare and are more easily available. This is because, as described above, it may be difficult to manufacture particles with a narrow particle size distribution. In one embodiment, Dmax may be, for example, any one of 1.5 to 2 μm, 1.5 to 1.85 μm, and 1.5 to 1.7 μm, although these are just examples of Dmax.
[0025] The specific surface area of the metal particles (A) is not particularly limited, but is preferably 0.8 to 1.7 m 2 / g, for example, 0.8 to 1.3 m 2 / g, 1.1-1.7m 2 / g, and 1.1 to 1.3 m 2 When the specific surface area of the metal particles (A) is in such a range, the bonding material has a viscosity suitable for application of an adhesion means such as printing or coating.
[0026] The specific surface area of particles, including metal particles (A), can be measured by known methods such as a permeation method and a gas adsorption method using gas molecules such as nitrogen.
[0027] In the bonding material, the ratio of the content of metal particles (A) to the total mass of the bonding material ([content of metal particles (A) in bonding material (parts by mass)] / [total mass of bonding material (parts by mass)]×100) is preferably 60 to 93 mass%, and may be, for example, any one of 70 to 93 mass% and 80 to 93 mass%. When the ratio is equal to or more than the lower limit, the bonding portion can be formed more efficiently. When the ratio is equal to or less than the upper limit, the fluidity of the bonding material is increased, and the handling property of the bonding material is improved.
[0028] <<Solvent>> The bonding material contains a solvent, so that the bonding material has fluidity and is easy to handle. The bonding material is typically in a paste or liquid form.
[0029] In this specification, unless otherwise specified, the term "solvent" is a concept that encompasses both a component that is liquid at room temperature and that dissolves a solute, and a component that is liquid at room temperature and that functions as a dispersion medium for dispersing a dispersoid. In this specification, "room temperature" means a temperature that is neither particularly cooled nor heated, that is, an ordinary temperature, and examples thereof include temperatures of 15 to 25°C.
[0030] The solvent is not particularly limited as long as it can be removed (vaporized) under heating conditions, and it is preferable that the solvent does not have reactivity with components other than the solvent, such as the metal particles (A) in the bonding material. Examples of the solvent include aromatic hydrocarbons such as toluene, o-xylene, m-xylene, and p-xylene; aliphatic hydrocarbons such as pentane, hexane, cyclohexane, heptane, octane, cyclooctane, nonane, decane, undecane, dodecane, tridecane, tetradecane, pentadecane, and decahydronaphthalene; halogenated hydrocarbons such as dichloromethane and chloroform; alcohols such as hexanol (e.g., 1-hexanol, etc.), heptanol (e.g., 1-heptanol, etc.), octanol (e.g., 1-octanol, etc.), nonanol (e.g., 1-nonanol, etc.), decanol (e.g., 1-decanol, etc.), benzyl alcohol, cyclohexanol, and terpineol (also known as terpineol); esters such as ethyl acetate, monomethyl glutarate, and dimethyl glutarate; ethers such as diethyl ether, tetrahydrofuran (THF), and 1,2-dimethoxyethane (dimethyl cellosolve); and monomethyl propylene glycol. Examples of such ethers include alcohol ethers (compounds having both a hydroxyl group and an ether bond in one molecule) such as ether (also known as 1-methoxy-2-propanol), 3-methoxy-3-methyl-1-butanol, and butyl carbitol (also known as diethylene glycol monobutyl ether); ketones such as acetone, methyl ethyl ketone (MEK), cyclohexanone, 2-octanone, and diisobutyl ketone (also known as 2,6-dimethyl-4-heptanone); hydroxyketones such as diacetone alcohol (also known as 4-hydroxy-4-methyl-2-pentanone); enones such as isophorone (also known as 3,5,5-trimethylcyclohex-2-en-1-one); nitriles such as acetonitrile; amides such as N,N-dimethylformamide (DMF) and N,N-dimethylacetamide; and alcohol esters (compounds having both a hydroxyl group and an ester bond in one molecule) such as texanol (2,2,4-trimethyl-1,3-pentanediol monoisobutyrate).
[0031] The bonding material may contain only one type of solvent, or may contain two or more types of solvents. When two or more types of solvents are contained, the combination and ratio thereof can be selected arbitrarily.
[0032] In the bonding material, the ratio of the solvent content to the total mass of the bonding material ([solvent content of bonding material (parts by mass)] / [total mass of bonding material (parts by mass)]×100) is preferably 7 to 40 mass%, and may be, for example, any one of 7 to 30 mass% and 7 to 20 mass%. When the ratio is equal to or more than the lower limit, the fluidity of the bonding material becomes higher, and the handleability of the bonding material becomes higher. When the ratio is equal to or less than the upper limit, the content of metal particles (A) in the bonding material can be increased, and the bonded portion can be formed more efficiently.
[0033] <<Other Ingredients>> The bonding material may or may not contain other components that do not fall under either the metal particles (A) or the solvent, as long as the effects of the present invention are not impaired. The other components are not particularly limited as long as they do not impair the effects of the present invention, and can be arbitrarily selected depending on the purpose.
[0034] The bonding material may contain only one type of other component, or two or more types. When there are two or more types, the combination and ratio thereof can be selected arbitrarily.
[0035] Examples of the other components contained in the bonding material include metal particles (B) other than the metal particles (A) and a resin component. That is, the bonding material may further contain either or both of the metal particles (B) and the resin component.
[0036] <Metal particles (B)> The metal particles (B) are different from the metal particles (A). In this embodiment, the fact that the metal particles (A) and the metal particles (B) are different from each other means that, for example, the metal species, particle size distribution, or shape of the two types of metal particles are different from each other. For example, when the metal type of metal particles (A) is silver, the metal type of metal particles (B) may be a metal type other than silver (e.g., copper).When the shape of metal particles (A) is approximately spherical, the shape of metal particles (B) may be other than approximately spherical (e.g., plate-like). The particle size distributions of two types of metal particles are different from each other, including cases where the D50s are different from each other and cases where the spreads of the particle size distributions are different from each other. When the D50s are different from each other, the particle size distribution of the mixture of the two types of particles will have two peaks of particle size. In addition, even if the D50s of the two types of particles are the same, the case where the spreads of the particle size distributions of the two types of metal particles are different from each other is also included in the case where the particle size distributions of the two types of metal particles are different from each other. The case where the spreads of the particle size distributions of the two types of metal particles are different from each other refers to, for example, at least one of Dmin, D10, D90, or Dmax. In other words, the case where the spread of the particle size distribution when the two types of particles are mixed is different from the spread of the tail of the particle size distribution of only one type of particle. The Dmin of the metal particles (B) is greater than 0.08 μm, and the bonding material does not need to contain metal particles (B) whose particle diameter is 0.08 μm or less. In other words, when the particle diameter of the metal particles (B) is measured on a volume basis by, for example, a laser diffraction / scattering type particle size distribution measurement, no particle diameter of 0.08 μm or less is observed.
[0037] The metal particles (B) are not particularly limited as long as they satisfy the above conditions. Examples of the metal species of the metal particles (B) include the same metal species as those of the metal particles (A). Examples of the metal particles (B) include metal particles having a shape other than approximately spherical; approximately spherical metal particles having a D50 of less than 0.3 μm; and approximately spherical metal particles having a D50 of more than 0.5 μm. A representative example of a shape of the metal particles (B) other than a substantially spherical shape is a plate shape.
[0038] In this specification, the term "plate-like" metal particles refers to a shape having two main surfaces, and the shape of the main surfaces is an approximately polygonal shape such as an approximately triangular shape (which is a triangular shape or a shape that can be regarded as a triangular shape), an approximately pentagonal shape (which is a pentagonal shape or a shape that can be regarded as a pentagonal shape), or an approximately hexagonal shape (which is a hexagonal shape or a shape that can be regarded as a hexagonal shape), or an irregular shape that can be regarded as having some sides or corners missing from the approximately polygonal shape. The thickness of the plate (i.e., the width between the two main surfaces, that is, the thickness of the plate in the direction perpendicular to the main surfaces) is 40 nm or less, and the maximum length of the two main surfaces (in other words, the particle diameter) is 10 to 1000 nm. The aspect ratio of the plate-like metal particles (=[maximum length of main surface (particle diameter)] / [width between main surfaces]) is 3 or more.
[0039] The metal species of the metal particles (B) contained in the bonding material may be only one type, or may be two or more types, and when there are two or more types, the combination and ratio thereof can be selected arbitrarily.
[0040] The metal species of the metal particles (B) is preferably silver or copper, and is preferably silver. Note that the metal species of the metal particles (B) is not limited to pure silver or pure copper, and may be a silver alloy or a copper alloy. It is preferable that the metal particles (A) and the metal particles (B) contained in the bonding material are both silver particles.
[0041] In the bonding material, the ratio of the content of the metal particles (B) to the total mass of the bonding material ([content of metal particles (B) in bonding material (parts by mass)] / [total mass of bonding material (parts by mass)]×100) is preferably 1 mass% or less, and may be, for example, 0.5 mass% or less, 0.3 mass% or less, or 0.1 mass% or less. When the ratio is equal to or less than the upper limit, the effect obtained by using the metal particles (A) is further enhanced.
[0042] When the volumetric particle size of the metal particles in the bonding material is measured by a laser diffraction / scattering particle size distribution measurement, if multiple peaks are observed in the particle size distribution, the presence of metal particles (B) can be confirmed. If the difference between D50 of metal particles (B) and D50 of metal particles (A) is relatively large, multiple peaks can be easily confirmed. When observing the bonding material with an SEM or the like, if metal particles having a shape other than a substantially spherical shape, such as a plate shape, are observed, the presence of metal particles (B) can be confirmed.
[0043] <Resin component> The resin component can be arbitrarily selected depending on the purpose and is not particularly limited. The resin component may be, for example, either a curable resin or a non-curable resin, or may be a thermoplastic resin. The resin component may be dissolved in a solvent or may be dispersed in a solvent. The resin component may be a binder that contributes to binding between metal particles or between a bonding material and an adherend, or may be spacer particles that are dispersed in a solvent and serve as spacers between metal particles. It should be noted that the resin provided on the surface of the metal particles for chemically treating the surface of the metal particles is not included in the resin component in this embodiment.
[0044] It is not essential that the bonding material of this embodiment contains a resin component (e.g., a binder or spacer particles). The content of the resin component is preferably as small as possible, and the ratio of the content of the resin component to the total content of the metal particles in the bonding material ([content of the resin component in the bonding material (parts by mass)] / [total content of the metal particles in the bonding material (parts by mass)]×100) is preferably less than 0.01% by mass, and may be 0.005% by mass or less. When the resin component is contained in an amount of less than 0.01% by mass, the resin component may be capable of lowering the porosity of the bonding material or suppressing the occurrence of cracks. However, if the resin component remains in the fired bonding material, the remaining resin component may increase the porosity. For this reason, it is preferable that the content of the resin component in the bonding material is less than 0.01% by mass, or that the bonding material does not contain a resin component. Therefore, it can also be said that the content of the resin component is preferably equal to or greater than 0 mass % and less than 0.01 mass %. When the ratio is less than 0.01 mass %, or when the dried bonding material does not contain a resin component, the effect of suppressing cracking of the dried bonding material even if the dried bonding material is thick, and the effect of forming a bonding portion with fewer voids even when the dried bonding material is fired while being pressurized at a low pressure are enhanced.
[0045] The resin component contained in the bonding material may be only one type, or may be two or more types. When there are two or more types, the combination and ratio thereof can be selected arbitrarily.
[0046] In the bonding material, when the metal particles include metal particles (A) and metal particles (B), the ratio of the content of the resin component to the total content of the metal particles (A) and the metal particles (B) is [content of the resin component in the bonding material (parts by mass)] / [total content of the metal particles (A) and the metal particles (B) in the bonding material (parts by mass)] × 100. Even in this case, the ratio of the content of the resin component is less than 0.01% by mass, and may be, for example, 0.005% by mass or less. Here, when the bonding material does not contain metal particles (B), the content of metal particles (B) in the bonding material is 0 parts by mass. Similarly, when the bonding material does not contain a resin component, the content of the resin component in the bonding material is 0 parts by mass.
[0047] The bonding material may contain, as the other component, a component (X) that does not fall into either the metal particles (B) or the resin component. In this case, in the bonding material, the ratio of the content of the component (X) to the total mass of the bonding material ([content of the component (X) (parts by mass)] / [total mass of the bonding material (parts by mass)]×100) is preferably 5% by mass or less, and may be, for example, 3% by mass or less or 1% by mass or less. When the ratio is equal to or less than the upper limit, the effect of suppressing cracking of the dried bonding material even if the dried bonding material is thick and the effect of forming a bonding part with fewer voids even if the dried bonding material is fired while being pressurized at a low pressure are enhanced. On the other hand, the content of the component (X) is 0 mass % or more.
[0048] In the bonding material, the ratio of the total content of the metal particles (A) and the solvent to the total mass of the bonding material ([total content of the metal particles (A) and the solvent in the bonding material (parts by mass)] / [total mass of the bonding material (parts by mass)]×100) is preferably 95% by mass or more, and may be, for example, 97% by mass or more or 99% by mass or more. When the ratio is equal to or more than the lower limit, the effect of suppressing cracking of the dried bonding material even if the dried bonding material is thick, and the effect of forming a bonding part with fewer voids even when the dried bonding material is fired while being pressurized at a low pressure are enhanced. On the other hand, the ratio of the combined content of the metal particles (A) and the solvent to the total mass of the bonding material is 100 mass % or less.
[0049] As described above, the bonding material according to this embodiment includes metal particles including substantially spherical metal particles (A) and a solvent for dispersing the metal particles, and has a particle diameter D50 of 0.3 to 0.5 μm at 50% cumulative volume of the metal particles (A) measured by laser diffraction / scattering particle size distribution measurement, and a minimum particle diameter Dmin of the metal particles (A) greater than 0.08 μm. In such a configuration, since D50 is in the range of 0.3 to 0.5 μm, cracks in the dried bonding material can be suppressed even if the dried bonding material is thick, and a bonding part with few voids can be formed even if the dried bonding material is fired while being pressurized at a low pressure of about 20 MPa or less. In addition, since the Dmin is greater than 0.08 μm, cracks in the dried bonding material can be suppressed even if the dried bonding material is thick. As a result, in a laminate in which the bonding material of this embodiment is sandwiched between conductive parts, even if the laminate is fired while being pressurized at a low pressure of about 20 MPa or less, a bonding portion with few voids can be formed.
[0050] The metal particles may include metal particles (B) different from the metal particles (A). The minimum particle size Dmin of the metal particles (B) measured by laser diffraction / scattering particle size distribution measurement is greater than 0.08 μm.
[0051] The solvent further contains a resin component which is a curable resin, a non-curable resin, or a thermoplastic resin, and the ratio of the content of the resin component to the content of the metal particles in the bonding material is less than 0.01 mass %. Alternatively, the bonding material does not contain a resin component which is a curable resin, a non-curable resin, or a thermoplastic resin in the solvent. This makes it possible to reduce the porosity of the bonding material and suppress the occurrence of cracks.
[0052] <<Method of manufacturing bonding material>> The bonding material of the present embodiment can be obtained by blending metal particles (A), a solvent, and, if necessary, the other components described above. After the components are mixed, the obtained material may be used as the bonding material as it is, or may be used as the bonding material after a known post-treatment or purification operation is performed as necessary.
[0053] The order in which the components are mixed is not particularly limited. The method for mixing the blend is not particularly limited, and may be appropriately selected from known methods such as a method for mixing by rotating a stirrer or agitator blades, etc.; a method for mixing using a mixer, a three-roll mill, a kneader, a bead mill, etc.; a method for mixing by applying ultrasonic waves, etc.
[0054] The temperature at which each component is mixed is not particularly limited as long as the components do not deteriorate, but a temperature of 0 to 40°C is preferable. The blending time of each component is not particularly limited as long as each blended component does not deteriorate, but it is preferably 10 minutes to 12 hours.
[0055] ◇ Manufacturing method of the joint A method for producing a bonded body according to one embodiment of the present invention is a method for producing a bonded body in which a conductive first part (sometimes simply referred to as a "first part" in this specification) and a conductive second part (sometimes simply referred to as a "second part" in this specification) are bonded to each other via a conductive bonding part (sometimes simply referred to as a "bonding part" in this specification), A step of attaching the bonding material according to the embodiment described above to a first surface of the first component or a second surface of the second component (sometimes referred to as an "attaching step" in this specification); A step of forming a dried bonding material by drying the applied bonding material (sometimes referred to as a "drying step" in this specification); a step of laminating the first component and the second component with the dried bonding material interposed therebetween to produce a laminate (sometimes referred to as a "lamination step" in this specification); and a step of forming the joint from the dried bonding material by firing the dried bonding material in the laminate at a temperature higher than the temperature at which the bonding material was dried (sometimes referred to as a "firing step" in this specification).
[0056] The conductive parts such as the first part and the second part are not particularly limited as long as they are conductive. Examples of the conductive parts include metal parts (metal members). The metal parts may be, for example, metal layers provided by sputtering or plating on the surface of a semiconductor chip or semiconductor element such as a silicon chip, or may be metal layers such as electrodes provided on a resin substrate or a ceramic substrate.
[0057] The joint is formed using the joint material according to the embodiment described above, and is a metal sintered body. For example, when the bonding material contains silver particles as the metal particles (A), the metal sintered body is a silver sintered body, and when the bonding material contains copper particles as the metal particles (A), the metal sintered body is a copper sintered body. The joint is electrically and thermally conductive, making it a useful alternative to solder.
[0058] In the above-mentioned production method, any of the steps can be carried out under atmospheric conditions. When the constituent material of either or both of the first and second components to be joined is a metal that is easily oxidized (e.g., copper, etc.), any of the steps in the manufacturing method may be performed in an inert gas atmosphere, such as nitrogen gas or helium gas.
[0059] Hereinafter, the method for producing the bonded body of the present embodiment will be described with reference to the drawings. First, a bonded body to which the manufacturing method of this embodiment is applied will be described.
[0060] <<zygote>> FIG. 1 is a cross-sectional view showing a schematic example of the bonded body. The bonded body 1 shown here is configured by bonding a conductive first component 11 and a conductive second component 12 via a conductive bonding portion 13. The first surface 11 a of the first component 11 is in contact with the joint portion 13 . The second surface 12 a of the second component 12 is in contact with the joint portion 13 . The joined body 1 is configured by stacking a first component 11, a joint 13, and a second component 12 in this order in the thickness direction. Hereinafter, the stacking direction of the first component 11, the joint 13, and the second component 12 will be referred to as the thickness direction.
[0061] The area of the first surface 11a of the first component 11 is preferably equal to or larger than the area of the second surface 12a of the second component 12.
[0062] The first component 11 has a sheet, plate or block shape.
[0063] The first component 11 is preferably configured to contain a metal, and more preferably is made of metal. Examples of metals that form the first component 11 include silver, copper, aluminum, gold, and nickel.
[0064] The first component 11 may be made of one layer (single layer) or may be made of two or more layers. When the first component 11 is made of multiple layers, these multiple layers may be the same or different from each other, and the combination of these multiple layers is not particularly limited. In this specification, not only in the case of the first part, "multiple layers may be the same or different" means "all layers may be the same, all layers may be different, or only some layers may be the same", and further, "multiple layers are different" means "at least one of the constituent materials and thicknesses of each layer is different from each other".
[0065] When the first component 11 is made up of a plurality of layers, for example, one or more layers on the bonding portion 13 side of the first component 11 may be layers that improve adhesion to the bonding portion 13 .
[0066] The thickness of the first component 11 can be set arbitrarily depending on the purpose of the joined body 1, and is not particularly limited. The thickness of the first component 11 may be, for example, 10 to 10,000 μm.
[0067] When the first component 11 is made up of a plurality of layers, the total thickness of the layers is preferably the thickness of the first component 11 described above.
[0068] Here, the first part 11 is shown to be in a sheet shape, a plate shape, or a block shape, but the first part 11 may be in a shape other than these, and the shape of the first part 11 can be selected arbitrarily depending on the purpose.
[0069] The second part 12 has a sheet, plate or block shape.
[0070] The second component 12 is preferably composed of a metal, and more preferably made of metal, and examples of metals constituting the second component 12 include the same metals as those constituting the first component 11 described above.
[0071] The second component 12 may be made of one layer (single layer) or may be made of two or more layers. When the second component 12 is made of multiple layers, these multiple layers may be the same or different from each other, and the combination of these multiple layers is not particularly limited.
[0072] When the second component 12 is made up of multiple layers, for example, one or more layers on the bonding portion 13 side of the second component 12 may be layers that improve adhesion to the bonding portion 13.
[0073] The thickness of the second component 12 can be set arbitrarily depending on the purpose of the joined body 1, and is not particularly limited. The thickness of the second component 12 is preferably 0.05 to 10,000 μm, and may be, for example, 0.05 to 500 μm, or may be greater than 500 μm and equal to or less than 10,000 μm. When the second component 12 is made up of a plurality of layers, the total thickness of the layers is preferably the thickness of the second component 12 described above.
[0074] Here, the second part 12 is shown to be in a sheet shape, a plate shape, or a block shape, but the second part 12 may be in a shape other than these, and the shape of the second part 12 can be selected arbitrarily depending on the purpose.
[0075] The joint 13 is in the form of a sheet, a plate or a block. The bonding portion 13 may be made of one layer (single layer) or may be made of two or more layers. When the bonding portion 13 is made of multiple layers, these multiple layers may be the same or different from each other, and the combination of these multiple layers is not particularly limited.
[0076] It is preferable that the entire surface of the joint portion 13 on the first component 11 side be in contact with the first surface 11 a of the first component 11 .
[0077] The thickness of the joint 13 may be, for example, 10 μm or more and less than 100 μm, but is preferably 100 μm or more, and may be, for example, 200 μm or more or 300 μm or more. When the thickness of the joint 13 is as thick as 100 μm or more, the thickness of the dried bonding material also needs to be 100 μm or more. When the thickness of the dried bonding material is thus thickened, the effect of the present invention, that is, cracking of the dried bonding material can be suppressed, is more significantly obtained by using the bonding material of this embodiment. On the other hand, the thickness of the joint 13 is preferably 400 μm or less in that the joint 13 can be formed more easily.
[0078] Here, the joint 13 is shown to be in a sheet, plate or block shape, but the joint 13 may be in any other shape, and the shape of the joint 13 can be selected arbitrarily depending on the purpose.
[0079] The area of the contact region of the joint 13 with the first component 11 (more specifically, the first surface 11a) and the area of the contact region with the second component 12 (more specifically, the second surface 12a) may be the same or different. The areas of the contact regions are each 9 to 2500 mm 2 It is preferable that the length is 9 to 1225 mm. 2 More preferably, for example, 9 to 576 mm 2 , and 9 to 144 mm 2 It may be either 225 to 1225 mm 2 , and 625~1225mm 2 It may be either 225 to 576 mm 2 However, these are just examples of the area of the contact area. When the area of the contact area is in the above-mentioned range, the bonding strength and heat dissipation between the components 11 and 12 and the joint 13 are increased.
[0080] The area of the second surface 12a of the second component 12 is preferably 50 to 150% of the area of the surface of the joint 13 on the second component 12 side. The area of the contact region with the joint 13 on the second surface 12a of the second component 12 is preferably 50 to 100% of the area of the entire second surface 12a. In joint 13, it is preferable that the entire surface on the first component 11 side is in contact with first component 11.
[0081] In the joined body 1, one first component 11 and one second component 12 are joined by one joint 13, but the joining form is not limited to this. In the joined body, for example, one first part and two or more second parts may be joined by one joint, in which case the two or more second parts may all be the same, all be different, or only partly different. In addition, in the joined body, for example, one first part and two or more second parts may be joined by two or more joining parts. In this case, the number of second parts and the number of joining parts may be the same or different. Furthermore, the two or more second parts may all be the same, all be different, or only some may be different. The numbers of first components and second components exemplified here may be reversed.
[0082] The bonded body to which the manufacturing method of the present embodiment is applied is not limited to that shown in FIG. 1. For example, the bonded body 1 shown in FIG. 1 may have some components changed, deleted, or added thereto without departing from the spirit of the present invention.
[0083] <<Porosity>> The porosity was measured by forming a cross section of the joint and observing the cross section using a scanning electron microscope (SEM). The observed joint 13 was a portion where the dried bonding material was sandwiched between the first surface 11a and the second surface 12a and sintered. That is, the porosity was measured in the joint 13 where the bonding material was sintered while being pressed at a predetermined pressure by the first component 11 and the second component 12. Here, the ratio of the area of the portions corresponding to the voids in the cross section to the area of the cross section ([area of the portions corresponding to the voids in the cross section] / [area of the cross section]×100) is defined as the "void ratio." For example, the ratio of the area of the portions corresponding to the voids in the region covered by a predetermined contour line to the total area of the region surrounded by the contour line in the cross section of the bonding portion 13 ([area of the portions corresponding to the voids in the region surrounded by the contour line] / [area of the region surrounded by the contour line]×100) may be defined as the "void ratio." The porosity is preferably 5% or less. By using the bonding material of this embodiment, even if the dried bonding material is fired while being pressurized at a low pressure of about 20 MPa or less, a bonding part with few pores (low porosity) can be formed. As is clear from the explanation of the method for calculating the porosity, the "cross-sectional area" in the formula for calculating the porosity includes not only the area of the metal sintered body itself but also the area of the area corresponding to the pores.
[0084] When determining the porosity of the joint, as described later in the examples, the cross-sectional image data obtained using an SEM is subjected to binarization processing using image processing software to identify the pores and calculate the porosity, thereby making it possible to calculate the porosity with higher accuracy.
[0085] When there is no bias in the location of the pores in the cross section, when determining the porosity of the joint, for example, the porosity may be calculated from each of the areas surrounded by a predetermined contour line in the SEM image data at several representative locations (e.g., 2 to 3 locations) on the cross section, and the average value thereof may be used as the porosity of the joint.
[0086] Next, the manufacturing method of this embodiment will be described by taking as an example the case of manufacturing the bonded body shown in FIG.
[0087] ◎Manufacturing method (1) 2A to 2E are cross-sectional views for illustrating a schematic example of a method for producing a bonded body of the present embodiment (sometimes referred to herein as "production method (1)"). In each figure, the same components as those shown in the figures already described are given the same reference numerals as in the figures already described, and detailed description thereof will be omitted.
[0088] <<Attachment process>> In the attaching step of the manufacturing method (1), the bonding material 130 is attached to the first surface 11a of the first component 11, as shown in FIG. 2A. The bonding material 130 may be attached to the first component 11 by a known method such as a printing method or a coating method.
[0089] Examples of the printing method include screen printing, flexographic printing, offset printing, dip printing, inkjet printing, dispenser printing, jet dispenser printing, gravure printing, gravure offset printing, and pad printing.
[0090] Examples of the coating method include methods using various coaters such as a spin coater, an air knife coater, a curtain coater, a die coater, a blade coater, a roll coater, a gate roll coater, a bar coater, a rod coater, and a gravure coater; methods using a wire bar; and methods using a coating device such as a slot die.
[0091] When bonding material 130 is applied to first component 11, a mask such as a metal mask plate may be used to apply bonding material 130 only to desired locations.
[0092] <<Drying process>> After the adhesion step of the manufacturing method (1), in the drying step, the adhered bonding material 130 is dried to form a dried bonding material 130', as shown in FIG. 2B. The drying process causes the solvent in the bonding material 130 to volatilize, so that in the dried bonding material 130 ′, there is no solvent or the amount of solvent contained is significantly reduced compared to the bonding material 130 .
[0093] The dried bonding material 130' is not a metal sintered body, and typically does not have the luster characteristic of metal. This external appearance characteristic also makes it possible to distinguish the dried bonding material 130' from the target metal sintered body.
[0094] The bonding material 130 can be dried by a known method, and is preferably dried by heating under normal pressure.
[0095] The heating temperature (drying temperature) of the bonding material 130 in the drying step can be appropriately adjusted depending on the type of solvent, but is preferably 70° C. or higher, and may be, for example, 100° C. or higher or 130° C. or higher. When the heating temperature is equal to or higher than the lower limit, the drying of the bonding material 130 proceeds more quickly. In addition, since the solvent can be sufficiently volatilized in the drying step, bumping due to residual solvent in the firing step described later can be prevented, and the occurrence of voids can be suppressed. On the other hand, the heating temperature is preferably 160° C. or less. By setting the heating temperature to the upper limit or less, deterioration of the dried bonding material 130′ is suppressed. For example, if the drying temperature is excessively high, the metal particles are necked (fused) together before the firing process, making it difficult to reduce the pores when pressurized.
[0096] The heating time (drying time) of the bonding material 130 in the drying step can be appropriately adjusted depending on the heating temperature, but is preferably 1 to 40 minutes, and may be, for example, either 3 to 30 minutes or 5 to 20 minutes. By keeping the heating time in such a range, the desired dried bonding material 130' can be formed more efficiently.
[0097] The thickness of the dried bonding material 130' may be, for example, 10 μm or more and less than 100 μm, but is preferably 100 μm or more, and may be, for example, 200 μm or more or 300 μm or more. When the dried material of a normal bonding material is thick, it is prone to cracking. In contrast, since the dried bonding material 130' uses the bonding material 130, cracking is suppressed even when the material is thick, such as 100 μm or more. On the other hand, the thickness of the dried bonding material 130' is preferably 400 μm or less in that the dried bonding material 130' is easier to form.
[0098] <<Lamination process>> 2C, in the lamination step after the drying step of manufacturing method (1), the first component 11 and the second component 12 are laminated with the dried bonding material 130' interposed therebetween to produce the laminated body 101. That is, the laminated body 101 is configured by laminating the first component 11, the dried bonding material 130', and the second component 12 in this order in the thickness direction, and the dried bonding material 130' is in close contact with the first component 11. The first component 11 is in contact with the dried bonding material 130' at the first surface 11a. The second component 12 is in contact with the dried bonding material 130' on the second surface 12a.
[0099] <<Firing process>> After the lamination step of manufacturing method (1), in the firing step, the dried bonding material 130' in the laminate 101 is fired at a temperature (sometimes referred to as the "firing temperature" in this specification) higher than the temperature at which the bonding material 130 was dried, as shown in FIG. 2D. When the bonding material 130 is dried by heating, the baking temperature of the dried bonding material 130' (the baking temperature) is set higher than the heating temperature of the bonding material 130 (the drying temperature).
[0100] The temperature rise rate of the dried bonding material 130' during firing is not particularly limited, but is preferably 30 to 70° C. / min, and may be, for example, 40 to 60° C. / min. When the temperature rise rate is in such a range, a metal sintered body (bonding portion 13) having the desired characteristics can be more efficiently manufactured.
[0101] The firing temperature of the dried bonding material 130′ (the temperature at which the metal particles (A) are sintered) is preferably 180° C. or higher, and may be, for example, any one of 200° C. or higher, 220° C. or higher, and 240° C. or higher. When the firing temperature is equal to or higher than the lower limit, a metal sintered body (bonding portion 13) with higher purity can be obtained. On the other hand, the firing temperature of the dried joining material 130' is preferably 320°C or less, in order to prevent excessive heating and obtain a metal sintered body (joint 13) with good characteristics, and may be, for example, either 300°C or less or 280°C or less.
[0102] The firing time of the dried bonding material 130' (the time for sintering the metal particles (A)) is preferably 3 to 120 minutes, and may be, for example, any one of 3 to 60 minutes, 50 to 90 minutes, and 80 to 120 minutes. When the firing time (sintering time) is within such a range, a metal sintered body having the desired characteristics can be produced more efficiently. In the firing step, it is preferable to fire the dried bonding material 130' at a firing temperature within the above-mentioned range and for a firing time within the above-mentioned range.
[0103] In the firing step, it is preferable to fire the dried bonding material 130' (sometimes referred to as "pressure firing" in this specification) while pressing the laminate 101 in the thickness direction. By pressing and firing the dried bonding material 130' in this manner, a bonding portion with fewer voids can be formed.
[0104] When the laminate 101 is pressed in the thickness direction, the pressure applied to the laminate 101 is a pressure P 1 and the pressure P applied from the second part 12 side. 2 and / or In this specification, "pressurization" means increasing the pressure applied to an object by actively applying force to the object, and does not mean, for example, that the object is only supported (just applying normal force) and no operation of actively applying force is performed. In the case of pressurization, for example, the position of the pressurizing means changes by itself with acceleration.
[0105] During pressurized firing, heating for firing the dried bonding material 130' (laminate 101) and pressurizing the dried bonding material 130' (laminate 101) may be started simultaneously, heating for firing the dried bonding material 130' may be started before pressurizing the dried bonding material 130' is started, or heating for firing the dried bonding material 130' may be started before pressurizing the dried bonding material 130' is started.
[0106] The pressure applied to the dried bonding material 130' during pressure firing is preferably 20 MPa or less, and may be, for example, 16 MPa or less. Normally, when the pressure during pressure firing is low, the number of voids in the bonded portion increases and a dense bonded portion cannot be obtained. However, by using the bonding material 130 of this embodiment, a dense bonded portion with few voids can be obtained even at a low pressure below the upper limit value. Furthermore, by keeping the pressure below the upper limit value, damage such as cracks and deformation of the first component 11 or the second component 12 are suppressed. On the other hand, the pressure during the pressurized sintering is preferably 1 MPa or more, for example, in order to effectively obtain the effect of the pressurization. Here, the pressure applied to the dried bonding material 130' (the pressure during pressurized firing) is the load applied to the laminate 101 during pressurization divided by the area of the dried bonding material 130' that is subjected to this load. 1 and the pressure P applied from the second part 12 side. 2 When both of the pressure and the pressure are applied to the bonding material 130′, the pressure during pressurized firing per unit area is (pressure P 1 / Pressure P 1 The area of the first surface 11a receiving the pressure P 2 / Pressure P 2(area of second surface 12a receiving the force).
[0107] 2E, the bonding part 13 is formed from the dried bonding material 130', and the desired bonded body 1 is obtained. The bonding part 13 is a metal sintered body formed from the bonding material 130 via the dried bonding material 130'.
[0108] By using the bonding material 130, the bonding portion 13 has few voids. Therefore, even if the temperature of the bonded body 1 fluctuates greatly, concentration of thermal stress is suppressed in the bonding portion 13, and damage to the bonding portion 13 is suppressed. Furthermore, since the bonding portion 13 is formed from metal particles having high thermal conductivity, the thermal conductivity of the bonding portion 13 is high.
[0109] So far, we have described a method for manufacturing a bonded body (manufacturing method (1)) in which the bonding material is adhered to a first surface of a first component and a bonded joint is formed from this bonding material. However, the manufacturing method of this embodiment may also be a method for manufacturing a bonded body (sometimes referred to in this specification as "manufacturing method (2)") in which the bonding material is adhered to a second surface of a second component and a bonded joint is formed from this bonding material.
[0110] ◎Manufacturing method (2) 3A to 3E are cross-sectional views for illustrating another example of the method for producing a bonded body of the present embodiment, that is, the production method (2).
[0111] <<Attachment process>> In the attaching step of the manufacturing method (2), the bonding material 130 is attached to the second surface 12a of the second component 12, as shown in FIG. 3A. The adhesion step in manufacturing method (2) can be performed in the same manner as the adhesion step in manufacturing method (1), except that the bonding material 130 is attached to the second surface 12a of the second component 12, rather than to the first surface 11a of the first component 11.
[0112] <<Drying process>> After the adhesion step of the manufacturing method (2), in the drying step, the adhered bonding material 130 is dried to form a dried bonding material 130', as shown in FIG. 3B. The drying step in manufacturing method (2) can be performed in the same manner as the drying step in manufacturing method (1), except that a second part 12 having bonding material 130 attached thereto is used instead of a first part 11 having bonding material 130 attached thereto. The dried bonding material 130' formed by manufacturing method (2) is the same as the dried bonding material 130' formed by manufacturing method (1), except that it is in contact with the second component 12 instead of the first component 11. In the manufacturing method (2), the dried bonding material 130' also uses the bonding material 130, so that cracks are suppressed even when the bonding material has a thickness of 100 μm or more.
[0113] <<Lamination process>> 3C, in the lamination step after the drying step of manufacturing method (2), the first component 11 and the second component 12 are laminated with the dried bonding material 130' interposed therebetween to produce a laminate 102. That is, the laminate 102 is configured by laminating the first component 11, the dried bonding material 130', and the second component 12 in this order in the thickness direction, and the dried bonding material 130' is in close contact with the second component 12. Laminate 102 is the same as laminate 101, except that dried bonding material 130' is in contact with second component 12 instead of first component 11. The lamination step in manufacturing method (2) can be performed in the same manner as the lamination step in manufacturing method (1), except that the first part 11 having the dried bonding material 130' is replaced with the second part 12 having the dried bonding material 130', and the first part 11 not having the dried bonding material 130' is replaced with the second part 12 not having the dried bonding material 130'.
[0114] <<Firing process>> After the lamination step of the manufacturing method (2), in the firing step, as shown in FIG. 3D, the dried bonding material 130' in the layered body 102 is fired at a temperature higher than the temperature at which the bonding material 130 was dried. The firing step in the manufacturing method (2) can be performed in the same manner as the firing step in the manufacturing method (1). In the firing step in the manufacturing method (2), it is also preferable to pressurize and fire the dried bonding material 130'.
[0115] By carrying out the firing step of manufacturing method (2), as shown in Fig. 3E, a joint 13 is formed from the dried joining material 130', and the intended joined body 1 is obtained. The joint 13 is a metal sintered body formed from the joining material 130 via the dried joining material 130'. The joined body 1 obtained by manufacturing method (2) is the same as the joined body 1 obtained by manufacturing method (1).
[0116] In the case of manufacturing method (2), the bonding portion 13 also has few voids due to the use of the bonding material 130. Therefore, even if the temperature of the bonded body 1 fluctuates significantly, the concentration of thermal stress is suppressed in the bonding portion 13, and damage to the bonding portion 13 is suppressed. Furthermore, since the bonding portion 13 is formed from metal particles having high thermal conductivity, the thermal conductivity of the bonding portion 13 is high. EXAMPLES
[0117] The present invention will be described in more detail below with reference to specific examples, although the present invention is not limited to the examples shown below.
[0118] The metal particles (A) and metal particles (B) used in the following examples and comparative examples are both silver particles produced by a reduction method.
[0119] [Example 1] << Manufacturing of bonding materials >> Metal particles (A)-1 (approximately spherical silver particles) (87 parts by mass) having the metal type, shape, particle size distribution, and specific surface area shown in Table 1 and Texanol (13 parts by mass) were weighed out into an agate mortar at room temperature and kneaded for 15 minutes. Next, the obtained kneaded material was passed through a triple roll three times to obtain the desired paste-like bonding material. FIG. 4 shows image data of metal particle (A)-1 at a magnification of 10,000 times obtained using a scanning electron microscope (SEM).
[0120] <<Manufacturing of joints>> <Formation of dried joint material and evaluation of its crack suppression effect> A silver-plated copper plate having a size of 20 mm×20 mm and a thickness of 1 mm and having a silver-plated layer having a thickness of 5 μm on its surface was prepared. A 300 μm thick metal mask was placed on the silver-plated surface of the silver-plated copper plate. A square shape measuring 7 mm x 7 mm was printed using an adhesive. This resulted in the adhesive in a square shape being attached to the surface of the silver-plated copper plate (attachment process). Next, the silver-plated copper plate with the bonding material attached was heated at 145°C for 15 minutes using a hot air oven to volatilize the Texanol in the bonding material, thereby drying it and forming a film-like dried bonding material with a rectangular planar shape (drying process). The dried bonded material was then visually observed and evaluated for crack suppression effect according to the following criteria. The results are shown in Table 1. [Evaluation Criteria] A: No cracks were observed in the dried bonding material, and the crack suppression effect was high. B: There are slight cracks in the dried bonding material, and the silver-plated copper plate cannot be seen through the cracks, but the crack suppression effect is poor. C: Cracks were clearly observed in the dried bonding material, and the silver-plated copper plate was visible through the cracks. The crack suppression effect was not observed or was low.
[0121] <Production of Joint> A back-side film-formed silicon carbide (SiC) chip was prepared, measuring 5 mm x 5 mm and 0.35 mm in thickness, with a 50 nm thick titanium film and a 100 nm thick silver film laminated in that order on one side (i.e. the back side) by sputtering. The entire exposed surface of the silver film in the silicon carbide chip having a film formed on its back side was overlapped on the side of the dried bonding material formed above opposite the silver-plated copper plate (i.e., the exposed surface), to produce a laminate in which the silver-plated copper plate, the dried bonding material, and the silicon carbide chip having a film formed on its back side were stacked in this order in the thickness direction (stacking process). Furthermore, in the laminate, a carbon sheet ("PERMA-FOIL (registered trademark)" manufactured by Toyo Tanso Co., Ltd.) was placed as a cushioning material on the surface of the silicon carbide chip in the silicon carbide chip having a film formed on its back surface.
[0122] Next, the laminate with the carbon sheet obtained above was pressed in the thickness direction using a servo press, and pressure was applied to the dried bonding material at a pressure of 15 MPa, and at the same time, heating was started at a temperature increase rate of approximately 50°C / min. At this time, the laminate with the carbon sheet was placed between a pair of press plates in the servo press. The pair of press plates includes a first press plate provided on the backside-coated silicon carbide chip side of the laminate with the carbon sheet, and a second press plate provided on the silver-plated copper plate side. The first press plate was fixed to the servo press. Then, the second press plate was moved toward the first press plate side, so that the laminate with the carbon sheet was supported by the first press plate, and pressure was applied to the laminate with the carbon sheet from the silver-plated copper plate side. That is, the laminate with the carbon sheet was pressed from the silver-plated copper plate side. Then, after the heating temperature (in other words, the temperature of the laminate) reached 250°C, this temperature was maintained for 5 minutes. That is, heating and pressurization were performed at a temperature of 250°C and a pressure of 15 MPa for 5 minutes. In this manner, the dried bonding material was pressurized and fired to form a bonded portion from the dried bonding material (firing process). Next, cooling was started by running cooling water inside the servo press, and when the temperature of the laminate reached 60° C., the pressure was released. The desired bonded body was obtained in this manner. The thickness of the bonded portion in the bonded body was greater than 100 μm.
[0123] <<Evaluation of zygotes>> <Evaluation of the effect of suppressing void generation in joints> The side surface of the bonded body obtained above was mechanically polished to form a cross section of the bonded body, and polishing marks were removed by flat milling treatment. Next, the cross section was observed at three random fields of view in the vicinity of the center of the joint in the width direction at an acceleration voltage of 4 kV and a magnification of 5000 times using a SEM. The image data obtained in this way was binarized using image processing software (Image J.), the black areas were classified as voids, and the porosity of the joint was calculated. The effect of suppressing the generation of voids in the joint was evaluated according to the following criteria. The results are shown in Table 1 together with the porosity. [Evaluation Criteria] A: The average porosity in three visual fields is 5% or less, and the effect of suppressing the generation of pores is high. B: The average porosity in three visual fields is greater than 5% and equal to or less than 10%, and the effect of suppressing the generation of pores is poor. C: The average porosity in three visual fields is greater than 10%, and no or a significantly low effect of suppressing pore generation is observed.
[0124] <<Production of bonding materials, production of bonded bodies, evaluation of bonded bodies>> [Example 2] A bonding material was produced and a bonded body was produced and evaluated in the same manner as in Example 1, except that metal particles (A)-2 (approximately spherical silver particles) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass) as shown in Table 1. The results are shown in Table 1. The thickness of the bonded part in the bonded body was greater than 100 μm. FIG. 5 shows imaging data of metal particle (A)-2 at a magnification of 10,000 times obtained using a SEM.
[0125] [Example 3] A bonding material was produced and a bonded body was produced and evaluated in the same manner as in Example 1, except that metal particles (A)-3 (approximately spherical silver particles) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass) as shown in Table 1. The results are shown in Table 1. The thickness of the bonded part in the bonded body was greater than 100 μm.
[0126] [Comparative Example 1] As shown in Table 1, a bonding material was produced and a bonded body was produced and evaluated in the same manner as in Example 1, except that metal particles (B)-1 (approximately spherical silver particles) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass). The results are shown in Table 1. The thickness of the bonded part in the bonded body was greater than 100 μm. FIG. 6 shows image data of metal particle (B)-1 at a magnification of 10,000 times obtained using a SEM.
[0127] [Comparative Example 2] As shown in Table 2, a bonding material was produced and a bonded body was produced and evaluated in the same manner as in Example 1, except that metal particles (B)-2 (approximately spherical silver particles) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass). The results are shown in Table 2. The thickness of the bonded part in the bonded body was greater than 100 μm. FIG. 7 shows imaging data of metal particle (B)-2 at a magnification of 10,000 times obtained using a SEM.
[0128] [Comparative Example 3] As shown in Table 2, a bonding material was produced in the same manner as in Example 1, except that metal particles (B)-3 (approximately spherical silver particles) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass), and a bonded body was produced and evaluated. The results are shown in Table 2. FIG. 8 shows imaging data of metal particle (B)-3 at a magnification of 10,000 times obtained using a SEM.
[0129] [Comparative Example 4] As shown in Table 2, a bonding material was produced in the same manner as in Example 1, except that metal particles (B)-4 ("N300", plate-shaped silver particles manufactured by Tokusen Kogyo Co., Ltd.) (87 parts by mass) were used instead of metal particles (A)-1 (87 parts by mass), and a bonded body was produced and evaluated. The results are shown in Table 2.
[0130] [Table 1]
[0131] [Table 2]
[0132] As is clear from the above results, in Examples 1 to 3, even if the dried bonding material was thick, cracking could be suppressed. Furthermore, even if the dried bonding material was fired while being pressurized at a low pressure of 15 MPa, a bonding part with few pores could be formed. In Examples 1 to 3, the porosity of the bonding part was 3.2% or less (2.6 to 3.2%).
[0133] In Examples 1 to 3, the bonding material contained only metal particles (A) as the metal particles, the D50 of the metal particles (A) was 0.32 to 0.48 μm, the Dmin of the metal particles (A) was 0.11 μm or more (0.11 to 0.19 μm), and the bonding material did not contain a resin component.
[0134] In Examples 1 to 3, the D90 of the metal particles (A) is 0.75 μm or less (0.52 to 0.75 μm), the D10 of the metal particles (A) is 0.21 μm or more (0.21 to 0.32 μm), and the specific surface area of the metal particles (A) is 0.95 to 1.5 m. 2 / g, which was assumed to result in the bonding material having more favorable properties.
[0135] In contrast, cracking of the dried bonding material could not be suppressed in Comparative Example 1. In Comparative Example 1, the bonding material contained metal particles (B) instead of metal particles (A). The Dmin of the metal particles (B) was 0.08 μm.
[0136] In Comparative Example 2, there were many voids in the joint, with a porosity of 6.6%. In Comparative Example 2, the joint material contained metal particles (B) instead of metal particles (A). The Dmin of the metal particles (B) was 0.08 μm, and furthermore, the D90 of the metal particles (B) was large at 0.82 μm.
[0137] In Comparative Example 3, the dried bonding material had significant cracks, and the silver-plated copper plate was visible through the cracks, making it impossible to manufacture a bonded body. In Comparative Example 3, the bonding material contained metal particles (B) instead of metal particles (A). The D50 of the metal particles (B) was 0.20 μm, which was too small, and the Dmin of the metal particles (B) was 0.06 μm, which was too small.
[0138] In Comparative Example 4, as in Comparative Example 3, the dried bonding material had significant cracks, and the silver-plated copper plate was visible through the cracks, so that a bonded body could not be manufactured. In Comparative Example 4, the bonding material contained metal particles (B) instead of metal particles (A). The metal particles (B) had a plate-like shape. [Industrial Applicability]
[0139] The present invention can be used in the manufacture of conductive junctions, particularly semiconductor devices. [Explanation of symbols]
[0140] 1...zygote, 11...first part, 11a...first surface, 12... second part, 12a... second surface, 13... Joint portion, 130... Joint material, 130'... Dried joint material, 101, 102... Laminate
Claims
1. A bonding material for bonding conductive parts together, Metal particles including substantially spherical metal particles (A); A solvent for dispersing the metal particles, The melting point of the metal of the metal particles (A) is 900 to 1100° C., The content ratio of the metal particles (A) to the total mass of the bonding material is 60 to 93 mass%, Measured by laser diffraction / scattering particle size distribution measurement. The metal particles (A) have a particle diameter D50 of 0.3 to 0.5 μm at 50% cumulative volume; The minimum particle diameter Dmin of the metal particles (A) is greater than 0.08 μm and less than 0.21 μm, The particle diameter D90 of the metal particles (A) at 90% cumulative volume is 0.45 μm or more and less than 0.8 μm. Bonding material.
2. The metal particles include metal particles (B) different from the metal particles (A), Measured by laser diffraction / scattering particle size distribution measurement. The minimum particle size Dmin of the metal particles (B) is greater than 0.08 μm, The metal particles (B) have a particle diameter D90 of less than 0.82 μm at 90% cumulative volume. The bonding material according to claim 1 .
3. The solvent further includes a resin component that is a curable resin, a non-curable resin, or a thermoplastic resin; The bonding material according to claim 1 , wherein a ratio of a content of the resin component to a content of the metal particles in the bonding material is less than 0.01 mass %.
4. The bonding material according to claim 1 or 2, wherein the solvent does not contain a resin component which is a curable resin, a non-curable resin, or a thermoplastic resin.
5. The bonding material according to claim 2 , wherein the metal particles (A) and the metal particles (B) are both silver particles.
6. The specific surface area of the metal particles (A) is 0.95 to 1.5 m 2 The bonding material according to claim 1 or 2, wherein the bonding strength is in the range of / g.
7. A method for manufacturing a joined body in which a conductive first component and a conductive second component are joined via a conductive joint, comprising the steps of: A step of attaching the bonding material according to claim 1 or 2 to a first surface of the first component or a second surface of the second component; drying the applied bonding material to form a dried bonding material; laminating the first component and the second component with the dried bonding material interposed therebetween to produce a laminate; and forming the bonded portion from the dried bonding material by firing the dried bonding material in the laminate at a temperature higher than a temperature at which the bonding material was dried.
8. The method for producing a joint body according to claim 7 , wherein the thickness of the joint is 100 μm or more.
Citation Information
Patent Citations
Joining material and joining method using the same
JP2011080147A
Silver-containing paste, and manufacturing method of bonded body
JP2022083624A
Method of Fabricating High-Power Module
US20200171578A1
Film-like firing material and film-like firing material with support sheet
WO2019163568A1